2021
DOI: 10.1002/mrm.28768
|View full text |Cite
|
Sign up to set email alerts
|

Automated renal segmentation in healthy and chronic kidney disease subjects using a convolutional neural network

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 35 publications
(63 reference statements)
2
35
1
Order By: Relevance
“…We achieved further improvement with quick manual adjustment of the CNN-segmentations. The Dice similarity metrics we achieved are comparable to what is reported for inter/intra-operator variability in manual organ segmentation (29). A possible refinement is to train the CNN to use both CT and SPECT information, which may be beneficial to identify cysts included in kidney contours (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…We achieved further improvement with quick manual adjustment of the CNN-segmentations. The Dice similarity metrics we achieved are comparable to what is reported for inter/intra-operator variability in manual organ segmentation (29). A possible refinement is to train the CNN to use both CT and SPECT information, which may be beneficial to identify cysts included in kidney contours (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Recent studies on machine learning‐based renal segmentation using neural networks reported processing times as good as 1 to 10 s per subject 76‐78 . Although these processing times are superior to our analytic approach, the effort needed to setup meticulously annotated imaging data that can be used to train, validate and test artificial intelligence algorithms must also be included in order to make a fair benchmarking of processing times.…”
Section: Discussionmentioning
confidence: 96%
“…55,[72][73][74][75][76] Recent studies on machine learning-based renal segmentation using neural networks reported processing times as good as 1 to 10 s per subject. [76][77][78] Although these processing times are superior to our analytic approach, the effort needed to setup meticulously annotated imaging data that can be used to train, validate and test artificial intelligence algorithms must also be included in order to make a fair benchmarking of processing times. Nevertheless, the processing time of the proposed ABSM can be substantially reduced by the application of state-of-the-art global optimization methods like evolutionary algorithms, swarm-based methods, or simulated annealing.…”
Section: Discussionmentioning
confidence: 99%
“…Manual kidney segmentation, such as region-of-interest (ROI) border tracing [ 20 ] or stereology [ 21 ] by experienced and qualified professionals, is considered the gold standard. However, because of the comparable signal intensities across the kidneys’ surrounding organs, and imaging artifacts, these manual methods are time-demanding (lasting 15–30 min) and might be skewed by investigator judgment [ 22 ]. An automated deep learning system that provides automatic segmentation would be a valuable supporting tool for clinicians [ 23 , 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…The proposed work focused on validating a Mask R-CNN for the automated segmentation of kidneys. In one study, a 2D convolutional neural network was applied to an MRI modality to segment left and right kidneys in healthy and chronic kidney disease subjects [ 22 ]. Timothy et al developed a convolutional neural network to apply an automated deep learning approach for cyst segmentation in MRI images [ 31 ].…”
Section: Related Workmentioning
confidence: 99%